Tracing the evolution of venom phospholipases A2 in Gloydius strauchii and related pitvipers: A tale of two acidic isozymes. (January 2018) - Yang, Zhang-min; Xie, Ying-zhe; Yan, Su-xian; Liu, Zhen-zhen; Song, Jian-cheng; Wang, Zhe-zhi; Tsai, Inn-Ho
Abstract: Two acidic Asp 49 -PLA2 s with Glu 6 substitution and a neutral Lys 49 -PLA (designated Gst-K49) were cloned from G. strauchii venom glands, their full amino acid sequences were deduced. The predominant acidic PLA2 (designated Gst-E6a) contains 124 residues and the M 18 W 30 substitutions, while the minor acidic PLA2 (designated Gst-E6b) contains 122 residues and the V 18 A 30 substitutions. Their sequences are most similar to those of the respective orthologous PLA2 s of G. intermedius venom. Gst-E6a and Gst-E6b appear to be paralogs and possibly have different predatory targets or functions. The LC-MS/MS results indicate the presence of only three PLA2 gene products in the crude venom, the relative expression levels were in the order of Gst-E6a ≫ Gst-E6b > Gst-K49, as confirmed by qPCR results. In contrast to other Gloydius, G. strauchii venom does not contain neurotoxic or basic anticoagulant Asp 49 -PLA2 s, but Gst-K49 is the first Lys 49 -PLA2 identified in Gloydius venoms. However, its venom content is relatively low and its pI value 7.3 is much lower than those of other Lys 49 -PLA2 s and. The Lys 49 -PLA2 genes appear to regress in the venom of most of Gloydius and related rattlesnake, and this evolutionary regression occurred before the dispersal of Asian pitvipers to the New World. Highlights: The hemorrhagic G. strauchii venom expresses two acidic PLA2 s but not crotoxin-like neurotoxins. Its acidic PLA2 s and a low expressed Lys49-PLA2 were cloned, sequenced and aligned with respective orthologs after BLAST. Among Gloydius venom studied, only G. strauchii expresses a Lys49-PLA2 with pI 7.3, which appear to undergo regression. Differential expression of either E6W30 or E6A30 PLA2 s could be related with the venom functional type and prey ecology. Venom dimorphism (hemorrhagic vs. neurotoxic) has existed early in ancestral Gloydius and their New world sister groups.